ASSESSMENT OF THE EFFICIENCY OF MANAGEMENT OF TRADE ENTERPRISES: A SCIENTIFIC-PRACTICAL APPROACH (Development Service Industry Management, 2025)
The relevance of this study is determined by the instability of the modern economic environment, the transformation of logistics processes, and shifts in consumer demand, which require trade enterprises to enhance their management efficiency and adaptability to market fluctuations. One of the key drivers of competitiveness is human capital, which provides innovation, operational flexibility, and service stability. For enterprises operating in the trade of electronics and household appliances, where competition unfolds both at the price level and in terms of service quality, the development of a management system capable of integrating financial and human resource dimensions becomes particularly significant. Despite a number of scientific contributions in the field of retail management, the issue of comprehensive evaluation of management effectiveness remains underexplored. In most cases, management systems are focused on solving operational tasks and fail to consider the strategic potential of human capital as a system-forming component of enterprise development. This underlines the need to establish a scientific and practical approach to integrated assessment of management effectiveness in trade enterprises. The purpose of this study is to develop and test a methodology for evaluating the effectiveness of trade enterprise management based on the combination of financial and human resource indicators. The proposed integrated approach includes the analysis of revenue dynamics, net profit, assets, and liabilities, along with human resource indicators such as labor productivity, profitability per employee, workforce dynamics, and staff turnover rates. To ensure comparability across enterprises, all indicators were normalized, enabling the calculation of an integrated index of management effectiveness.The empirical assessment, carried out using data from leading Ukrainian retail companies (“Rozetka,” “Moyo,” “Epicenter,” “Allo,” “Comfy,” “Foxtrot”), demonstrated that enterprises with consistent financial and HR policies achieved the highest levels of stability and predictability. In contrast, high volatility of the integrated indicators in several companies revealed the need for stronger HR policies and the implementation of staff retention programs. The study concludes that the developed methodology provides a comprehensive quantitative assessment of management effectiveness and can serve as an effective tool for monitoring, benchmarking, and supporting the strategic development of trade enterprises under turbulent market conditions.
Keywords: human capital; retail enterprises; efficiency; management; integral evaluation; financial indicators; personnel policy; staff turnover; personnel; scientific and practical approach; financial and economic support; personnel support